Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/jcb.29026
|View full text |Cite
|
Sign up to set email alerts
|

miR‐4319 inhibited the development of thyroid cancer by modulating FUS‐stabilized SMURF1

Abstract: Thyroid cancer, a common type of endocrine system cancer, has witnessed rising incidence and deaths over the past few years. The role of microRNAs is being increasingly discovered in a variety of cancers, including thyroid cancer. miR‐4319 has been elucidated in several studies to exert an antitumor function in multiple cancers but has never been explored in thyroid cancer. Our study proposed to explore the function and modulatory mechanism of miR‐4319 in thyroid cancer. First, we confirmed the downregulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Combined with results from starBase and our experiments, FUS was identified as the RBP for LDHB. RBP FUS has been discovered to act as a tumor enhancer in several cancers such as thyroid cancer, non-small cell lung cancer and glioma [26][27][28]. Apart from the verified affinity between FUS and LDHB, it was also revealed that FUS could elevate the stability of LDHB mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with results from starBase and our experiments, FUS was identified as the RBP for LDHB. RBP FUS has been discovered to act as a tumor enhancer in several cancers such as thyroid cancer, non-small cell lung cancer and glioma [26][27][28]. Apart from the verified affinity between FUS and LDHB, it was also revealed that FUS could elevate the stability of LDHB mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a group of small singlestranded RNAs consisting of 22 nucleotides with a typical hairpin secondary structure [7]. They modulate gene silencing via directly targeting at an mRNA for degeneration or repressing translation [8]. A change in miRNA expression is related to different kinds of malignancies, such as EOC [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, miR-4319 is transcriptionally modulated by PLZF and acts as a tumour suppressor in CRC (colorectal cancer) via targeting ABTB1 21. MiR-4319 suppresses the development of thyroid cancer by regulating FUS (fused in sarcoma)-stabilized SMURF1 (SMAD-specific E3 ubiquitin protein ligase 1) 25. Nevertheless, the biological effects and the latent regulatory mechanism of miR-4319 in HCC remain obscure and need to be further elucidated.…”
Section: Introductionmentioning
confidence: 99%